Predictive Value of Platelet-to-Lymphocyte Ratio and Neutrophil-to-Lymphocyte Ratio in Patients with Hypersensitivity Pneumonia: Platelet-To-Lymphocyte Ratio And Neutrophil-To-Lymphocyte Ratio In Hypersensitivity Pneumonia - Demirci Üçsular, Fatma; Polat, Gulru; Karadeniz, Gülistan; Ayrancı, Aysu; Keskin, Merve; Büyükşirin, Melih; Güldaval, Filiz; Yalnız, Enver (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Aim: To evaluate Platelet-to-Lymphocyte Ratio (PLR) and Neutrophil-to-Lymphocyte Ratio (NLR) in patients with HP. Method: A sample of 140 total patients, 50 having chronic HP and 20 having acute HP, and a control group of 70 more patients were included in this retrospective study conducted with hospital Ethical Committee approval. Results: PLR and NLR values ​​were significantly higher in all HP patients than in the control group ( p <0.001). In addition, these biomarkers were significantly higher in patients with acute HP than in the chronic HP group (p = 0.017 and p = 0.044, respectively). The cutoff values ​​for PLR and NLR were: • 177 (p = 0.020) and 2.76 (p <0.0001) between the HP patients and the control group, and, • 110 (p = 0.0054) and 2.15 (p = 0.03), between the acute and chronic HP groups. Conclusion: PLR and NLR values ​​are inexpensive and easy parameters that can guide in diagnosing hypersensitivity pneumonia and the acute-chronic differentiation of the disease.